2004
DOI: 10.1002/jsfa.1910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymes in diets with varying energy levels on growth and egg production performance of Japanese quail

Abstract: The present study was conducted to evaluate the effect of feed-grade enzyme supplementation in diets with varying levels of energy on the performance of growing and laying Japanese quails. Day-old Japanese quails, 504 in number, were subjected to six dietary treatments with six replicates at each treatment. Each replicate had 14 chicks. The dietary treatments consisted of three energy levels ie 12.15 MJ (2900 kcal), 11.30 MJ (2700 kcal) and 10.48 MJ (2500 kcal) ME kg −1 diet and two enzyme levels (0 and 0.5 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
10
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
9
10
1
Order By: Relevance
“…FI differed significantly (P b 0.01) due to dietary energy levels, and reduced linearly (P b 0.01) with the increase in energy levels during 0-3 or 0-5 weeks of age. These results were in line with those of other workers (Elangovan et al, 2004). A higher FI with decrease in dietary energy concentration was to compensate energy intake.…”
Section: Feed Intakesupporting
confidence: 94%
See 2 more Smart Citations
“…FI differed significantly (P b 0.01) due to dietary energy levels, and reduced linearly (P b 0.01) with the increase in energy levels during 0-3 or 0-5 weeks of age. These results were in line with those of other workers (Elangovan et al, 2004). A higher FI with decrease in dietary energy concentration was to compensate energy intake.…”
Section: Feed Intakesupporting
confidence: 94%
“…The FCR improved linearly (P b 0.01) at both the growth phases (0-3 and 0-5 weeks) with increase in dietary energy level, and the best (P b 0.01) FCR was emerged from diet with 12.97 MJ ME kg − 1 . An improvement in FCR in growing quails with increasing dietary energy level was also reported earlier (Elangovan et al, 2004). FCR improved with increase in EAA level during 0-3 weeks of age.…”
Section: Feed Conversion Ratiosupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, a dietary level of 2700 kcal/kg and high EAA (25.8-26.0% CP) during the 0-5 weeks of age was found optimum for body weight gain. Live weight gain also did not differ among diets with 2900 or 2700 kcal ME/kg during 0-5 weeks [24] or 11.72-13.39 MJ ME/kg during 0-6 weeks of age [25]. The quails responded beneficially to high EAA level (25.8-26.0% CP) which was in line with the earlier feeding trial with heavy body weight line of quails [7].…”
Section: Live Weight Gainsupporting
confidence: 73%
“…A few reports on growing quails showed that dietary AME did not significantly affect growth rate (Elangovan et al., ; Kaur et al., , ; Tarasewicz et al., ; Mosaad and Iben, ), suggesting that quail chicks might normally grow at even low levels of dietary AME that ranged from 2800 to 3100 kcal/kg. However, Ghazaghi et al.…”
Section: Discussionmentioning
confidence: 99%